Perceived Value, Influencer Advertising, and Engagement for Enhanced Customer Loyalty and Advocacy - Teguh Maianto; Sukesi Sukesi; Liosten RR.Ully Tampubolon; Aminullah Assagaf; Slamet Ryadi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how influencer marketing and customer engagement enhance loyalty and advocacy, with perceived value as a key mediator, to clarify the mechanisms behind these effects in a competitive digital landscape. Methodology: Using a quantitative survey of active online consumers, this study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct effects of influencer-based advertising and customer engagement on perceived value, loyalty, and advocacy, as well as the mediating role of perceived value. Results: The findings demonstrate that both influencer-based advertising (? = 0.452, p < 0.001) and customer engagement (? = 0.384, p < 0.001) significantly boost perceived value. In turn, perceived value significantly mediates the impact of these antecedents on customer loyalty and advocacy, highlighting its critical intermediary role. Notably, while influencer marketing and engagement exert strong direct effects on loyalty, only customer engagement, and not influencer marketing, directly influences advocacy. Conclusions: Influencer-based advertising and customer engagement increase perceived value, strengthening loyalty and advocacy; however, only customer engagement directly influences advocacy. Limitations: This study's cross-sectional methodology records data at only one particular moment, making it more difficult to identify changes over time and to draw conclusions about causal linkages. Contributions: This research contributes to marketing theory and practice by pinpointing perceived value as the essential conduit linking marketing stimuli to lasting customer behaviors. It offers empirical evidence that both influencer strategies and engagement foster loyalty and advocacy principally by enhancing perceived value.